Gender Diversity at the Board Level Can Mean Innovation Success - Cheng, J.; Groysberg, Boris (MIT Sloan Management Review, 2020)
Recruiting women directors can create positive feedback loops that pave the way for future diversity, and strengthen a board's role in supporting long-term innovation and creativity.
Online resource; Title from title page (viewed January 22, 2020)
Keywords: Leadership in women; Businesswomen; Women executives; Leadership chez la femme